2006
DOI: 10.1111/j.1468-2982.2006.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Genetic Risk Factors for Migraine in Children

Abstract: Migraine can induce ischaemic stroke, and is considered an independent risk factor for stroke in the young. To date, the nature of the link between migraine and stroke is essentially unknown. Forty-five children were studied. Homocysteine levels (fasting and post methionine load), vitamin B12 and plasma folate levels, factor V Leiden, factor II G20210A, methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C mutations were examined. Compared with controls, patients with migraine had higher levels of post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 31 publications
2
65
1
Order By: Relevance
“…), but not in the Estonian population. A trend for migraine was reported in Italian patients who were 677TT and 1298CC homozygous carriers [24]. In the Croatian pediatric migraine population, no statistically significant association with migraine in carriers of 677CT polymorphism was found, but a trend toward an increased risk for migraine in patients who had homozygous variant 677TT was found [25].…”
Section: Introductionmentioning
confidence: 91%
“…), but not in the Estonian population. A trend for migraine was reported in Italian patients who were 677TT and 1298CC homozygous carriers [24]. In the Croatian pediatric migraine population, no statistically significant association with migraine in carriers of 677CT polymorphism was found, but a trend toward an increased risk for migraine in patients who had homozygous variant 677TT was found [25].…”
Section: Introductionmentioning
confidence: 91%
“…In a study of Bottini et al was analyzed the prevalence of homozygous variant of an Italian study population, it was identified a trend towards an increased incidence of migraine in subjects who carried the mutation [8]; another study examined a group of Croatian pediatric patients suffering from migraine, the 677TT genotype was associated with an higher risk of migraine [11]. No association was found in Spanish and Portuguese migraineurs with TT genotype [10,12,13] Lorenz et al analyzed MTHFR 677TT polymorphism in a group of Estonian pediatric migraineurs and did not detect a close link with migraine prevalence [14] MTHFR C677T variant differently occur in different countries, so it could be considered an ethnic-specific polymorphism [14].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analisys of 15 case control studies showed a close correlation between TT variant and Caucasians suffering from MA, in non-Caucasian population this genotype is associated with total migraine [11]. In a study of Bottini et al was analyzed the prevalence of homozygous variant of an Italian study population, it was identified a trend towards an increased incidence of migraine in subjects who carried the mutation [8]; another study examined a group of Croatian pediatric patients suffering from migraine, the 677TT genotype was associated with an higher risk of migraine [11]. No association was found in Spanish and Portuguese adult migraineurs [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations